Evaluation of hematological markers (TLC, neutrophil count) and CRP protein in early diagnosis of neonatal sepsis, taking blood culture as gold standard - Huma, Zille; Farooque, Muhammad Abid; Rafiq, Muhammad Yasir; Hussain, Chahat; Younas, Asif; Faizan, Syed Muhammad (Infectious Diseases Journal of Pakistan, 2025)
Background: Neonatal sepsis is one of the major causes of neonatal mortality and morbidity. This study was done to determine the accuracy of TLC and Neutrophil count for early diagnosis of neonatal sepsis and to determine the diagnostic accuracy of C-Reactive protein (CRP) for early diagnosis of Neonatal sepsis. Material and Methods: It was a cross-sectional study performed in Microbiology department, of a tertiary care Hospital, Lahore. A total of 241 blood samples were collected in the blood culture bottles, incubated and inoculated on blood and MacConkey agar plates. Final identification was performed using API and VITEK2. Antimicrobial susceptibility testing (AST) was performed according to CLSI 2024. Results: Out of total 241 study subjects, 150(62%) were males and 91(38%) were females. 49 (20.3%) blood culture were positive. Among the isolated microorganisms, Acinetobacter baumannii 8(16.3%), Acinetobacter jhonsonii 3(6.1%), coagulase negative Staphylococci 15(30.6%), Methicillin resistant Staphylococci 3(6.1%), Enterococcus faecalis 3(6.1%), Klebsiella pneumoniae 8(16.3%), Listeria monocytogenes 1(2.0%), Pseudomonas aeruginosa 2(4.1%), and Serratia marcescens 6(12.2%) were seen. Majority of the gram-positive bacteria were resistant against penicillin, and sensitive to vancomycin and linezolid. Whereas, the gram-negative bacteria are most resistant to ampicillin, least resistant noted against carbapenems. Conclusion: The present study aims to identify the role of hematological indicators as TLC, DLC and CRP, as early indicator of neonatal sepsis. The results of the hematological markers and serum CRP received in a much less time as compared to the blood culture that gives results after the delay of 4 days. Keywords: Neonatal sepsis, TLC, CRP, Rapid diagnosis